Promoting positive education and care transitions for children - Rosier, K; McDonald, M (My University, 2011)
This Resource Sheet is a review of research regarding children’s transition from home, to early childhood education and care services and then to school, with a specific focus upon both children and parents’ experiences of those transitions. The factors that influence a child’s ability to adapt to school are considered and case studies of promising transition programs are provided.
Keywords: Education and Training; Learning, education and training; Education and Training; Learning, education and training